2005
DOI: 10.3748/wjg.v11.i3.336
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ST13 in colorectal cancer and adjacent normal tissues

Abstract: The expression of ST13 decreases in colorectal cancer tissue compared with that in adjacent normal tissue. ST13 is mostly expressed in colorectal epithelia and adenocarcinoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…ST13 (suppression of tumorigenicity 13) maps to chromosome 22q13.2 and was reported to be down-regulated in CRC tissue when compared with its expression in adjacent normal tissue. 58 Bi-allelic mutations of p300, a transcriptional co-activator binding E1A also localized to chromosome 22q13.2, have been shown in several human cancers. In particular, this gene seems to function as a tumor suppressor gene in the intestinal epithelium, 59 and mutations in its coding region are found at high frequency among CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…ST13 (suppression of tumorigenicity 13) maps to chromosome 22q13.2 and was reported to be down-regulated in CRC tissue when compared with its expression in adjacent normal tissue. 58 Bi-allelic mutations of p300, a transcriptional co-activator binding E1A also localized to chromosome 22q13.2, have been shown in several human cancers. In particular, this gene seems to function as a tumor suppressor gene in the intestinal epithelium, 59 and mutations in its coding region are found at high frequency among CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, ST13 expression was lower in colorectal cancer tissues compared with the tumor-adjacent normal mucosa specimens (Wang et al, 2005). The previous study showed that ST13 re-expression mediated by oncolytic adenovirus within colorectal cancer cells can induce cell apoptosis and exert potent antitumour efficacy in colorectal cancer xenografts in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have proved that ST13 mRNA and protein levels were lower in colorectal cancer tissues compared with adjacent normal tissues (Mo et al, 1996;Zheng et al, 1997;Dong et al, 2005;Wang et al, 2005). Moreover, increased ST13 protein expression suppressed proliferation of colorectal cancer cells and induced apoptosis in colorectal cancer cell lines (Yang et al, 2008;Yu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…По данным литературы [21], ген ST13 ингибиру-ет опухолевый рост при различных видах рака. По-нижение экспрессии ST13 может приводить к риску развития карциномы желудка и колоректальной кар-циномы.…”
Section: результаты и обсуждениеunclassified